Applications of the fractional Sturm-Liouville difference problem to the fractional diffusion difference equation - Malinowska, Agnieszka B.; Odzijewicz, Tatiana; Poskrobko, Anna (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with homogeneous and non-homogeneous fractional diffusion difference equations. The fractional operators in space and time are defined in the sense of Grünwald and Letnikov. Applying results on the existence of eigenvalues and corresponding eigenfunctions of the Sturm-Liouville problem, we show that solutions of fractional diffusion difference equations exist and are given by a finite series.
Keywords: anomalous diffusion; fractional diffusion equations; fractional calculus; difference equations